Legal and Ethical Analysis of The Implementation of Informed Consent in Medical Practice in Indonesia - Dewi, Gusti Ayu Made Purnama; Adiatmika, I Putu Gede (Babali Nursing Research, 2025)
Introduction: Implementing informed consent in medical practice in Indonesia is fundamental to protecting patients' rights, but it is not quite enough to answer the law’s power. Research This analyzes the legal and ethical aspects of the application of informed consent in medical practice in Indonesia, with a review of applicable laws and regulations and principles of the underlying bioethics.Methods: This study used a normative juridical and qualitative descriptive approach to analyze legal and ethical aspects of informed consent in medical practice. Data were obtained from 15 secondary sources, including laws, academic literature, and court decisions, and analyzed qualitatively. Source triangulation linking legal, health, and bioethical perspectives was applied to ensure validity. The study aims to contribute theoretically and practically to improving informed consent policy and practice.Results: Research results show that although the regulation related to informed consent is sufficiently comprehensive, there are still challenges in its implementation, such as a lack of understanding of the patient, limitations in the time doctors have to give adequate information, and aspects of culture that influence the decision-making process in medical care.Conclusion: Improvement in socialization, education for power medical and patient, and strengthening of the regulations are required to ensure informed consent can be obtained and applied effectively and fairly in medical practice in Indonesia.Keywords: word; another word; lower case except names